Ռափայել Պատկանյանը՝ երգիծաբան. «Նոր Նախիջևանի քնար» - Լուսյա Հարությունյան (ՀՀ ԳԱԱ հրատ.)
Автор придавал большое значение своим произведениям, написанным на ново-нахичеванском диалекте, в особенности подчеркивая их воспитательную роль. Эти работы он считал олицетворением жизненных образов, зеркальным отображением критического отношения к действительности. Бесконечны и разнообразны способы и приемы, с помощью которых поэт мог раскрыть одну и ту же тему..The author gave a great importance to the works written in the dialect of new Nakhichevan, underlining especially their educative role. He considered these works to be truthful images of life, undeceitful reflection of the critical attitude to reality. The most important here is the author’s amazing comic talent of great strength, which enabled him to find the extremely varied, unique satirical methods, revealing the life of the elite from different angles.
Keywords: Language and Literature